Dakwah Argumentatif Ustadz Adi Hidayat di Media Sosial Youtube - Rahma Alfiah; Syahrul Fauzi Bisri; Nurul Fauzia (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah UIN Sultan Maulana Hasanuddin Banten, 2022)
This research aims to find out the analysis of argumentative da'wah contained in Ustadz Adi Hidayat's video lectures on the YouTube channel using content analysis. The questions to be answered are: a) What is the analysis of Ustadz Adi Hidayat's argumentative preaching, in lectures that are broadcast via social media Youtube? b) What is the content of Ustadz Adi Hidayat's da'wah message? The type of research used is a type of qualitative research. The data sources are primary data sources and secondary data sources, and this research uses data collection techniques with observation and documentation methods. in this study it was found that there was a tendency in Adi hidayat's da'wah to contain arguments that strengthen belief.